The impact of women’s individualization on commercial insurance purchase behavior: evidence from China - Wang, Li; Gao, Lifei; Liu, Shuixing; Li, Wenzhong; Bai, Yunpeng (Frontiers in Public Health, 2025)
IntroductionWomen’s individualization, which enables them to become unshackled from their family bondage and become more independent, amplifies exposure to occupational hazards, gender discrimination, work–family conflicts, and health risks, increasing the need for risk mitigation. Providing pioneering empirical evidence, this study quantifies how individualization reshapes Chinese women’s commercial insurance demand by integrating social theory with risk management principles.MethodsBased on the latest three-wave data from the China Comprehensive Social Survey, we analyze the impact of women’s individualization on commercial insurance purchasing behavior using various methods such as the probit model, instrumental variable method, and propensity score matching.ResultsWomen’s individualization can significantly increase the probability of purchasing commercial medical insurance by 1.430% and commercial endowment insurance by 0.743%. This effect operates through heightened risk management awareness, increased purchasing power, and enhanced cognitive ability. The impact is stronger among employed women, those with higher wealth, poorer health, younger and middle-aged women, and women in central and eastern China.ConclusionThis study reveals that women’s individualization motivates them to transfer personal risks through insurance purchasing, demonstrating how social transformation shapes financial decision-making. Crucially, findings inform stakeholders: policymakers are advised to prioritize insurance subsidies for vulnerable women and adapt regulations to regional market needs. Insurers should innovate tailored products addressing individualized women’s distinct risk profiles. Women should proactively mitigate personal risks through tailored insurance solutions. Researchers are offered a novel framework linking social transformation to financial behavior, urging further cross-cultural investigation.